Workshop on STM32 Board Utilization to Elevate the Expertise of Electrical Vocational High School (SMK) Teachers in the Greater Bandung Region - Somantri, Maman; Pramudita, Resa; Rizqulloh, Muhammad Adli; Pawinanto, Roer Eka (REKA ELKOMIKA: Jurnal Pengabdian kepada Masyarakat, 2024)
The STM32 microcontroller technology workshop, held in the Greater Bandung region, was a pioneering initiative aimed at enhancing the skills of vocational high school educators. It provided in-depth knowledge and practical experience in advanced STM32 features like GPIO, ADC, PWM, and UART communication. The workshop employed an active, participant-focused approach, ensuring impactful learning. Feedback was overwhelmingly positive, with high satisfaction rates in content quality (83.5%), delivery method (81.75%), and hands-on activities (79.25%). However, suggestions for improvement included better preparatory materials and post-workshop support. Overall, the workshop marked a significant step in advancing the professional development of educators and elevating the quality of technical and vocational education in the region.